Health information prescription system for non communicable diseases: a systematic review and thematic analysis - Abdolahad Nabiolahi; Shahram Sedghi; Rokhsareh Aghili; Leila Nemati-Anaraki (Russian Open Medical Journal, 2020)
Objective ― Prescribing health information is very important to empower informed patients. The goal of present study is to recognize challenges for developing health information prescription on non-communicable diseases. Material and Methods ― Six data bases related to health information prescription were investigated. They included Web of Science, Scopus, PubMed, Google Scholar, Ovid and EMBASE. The investigated studies were published from 2000 to 2019. The language of the articles was English and the access to full text was one of the inclusion criteria. The research was evaluated by Prisma checklist and critical apprising. Different dimensions of health Information prescription system were recognized by thematic analysis. Results ― 54 studies were recognized based on the inclusion criteria. The results showed that there were three main concepts related to primary dimensions of the system in designing health information prescription system: determination of system functional goals, recognition of implementation barriers and recognition of developmental sub-structures. There were 16 subcategories including primary goals for accessibility, the concerns related to patients information confidentiality, individual differences and interests and personalizing the process of information prescription, the lack of integrity in health Information system for providing pattern of health Information system related to diabetic patients. Conclusion ― The goals, implementing barriers and functional substructures of health information prescription system should be recognized in order to improve self-care behaviors of diabetic patients in clinic. It is recommended that the future investigations focus on research gaps in personalizing health information prescription and integration of health information prescription process in health care system.